The effect of post-abortion care (PAC) on anxiety in women with spontaneous abortion based on MicroRNA-21 expression, cortisol level, and Fordyce happiness pattern - Gong, Leilei; Han, Jun; Yan, Wenwen; Qin, Yichen (Cellular and Molecular Biology, 2022)
Abortion is one of the most common complications in pregnancy, and the cause of its occurrence in many cases remains unknown. The high prevalence and consequences of anxiety in women with spontaneous abortion could highlight the importance and role of post-abortion care (PAC). Detection and identification of biomarkers related to abortion and anxiety can effectively diagnose and prevent complications. Among the known biomarkers, microRNAs and the cortisol level have high potential. Therefore, the present study evaluated the effect of post-abortion care (PAC) on anxiety in women with spontaneous abortion based on MicroRNA-21 expression, cortisol level, and Fordyce happiness pattern. In this randomized clinical trial, 72 women with spontaneous abortion were studied and randomly divided into two groups of intervention (n = 36) and control (n = 36). Data were collected through a demographic questionnaire and HADS. To assess PAC, the intervention group was consulted in 8 sessions of 60 minutes in the first 72 hours after abortion. Meetings were held twice a week for four weeks. Both groups were followed up immediately after and one month after the intervention. To evaluate biological factors, 4ml of blood sample was obtained from the subjects. Blood cortisol levels were measured by the Cortisol Competitive Human ELISA Kit (Thermo-Fisher, USA), and microRNA-21 evaluation was performed by Real-time PCR technique. Data were analyzed using SPSS16 software. Results showed that before the intervention, there was no significant difference in the mean score of anxiety between the control and intervention groups (P> 0.05); But at the time immediately and one month after the intervention, there was a significant difference in the mean score of anxiety (p <0.001). The results of biological factors evaluation showed that in the intervention group, serum cortisol levels and microRNA-21 expression decreased significantly (p <0.05). In general, PAC based on the happiness pattern can control the anxiety of women with spontaneous abortion. Therefore, it is recommended as an effective and non-invasive intervention in preventing women's psychological problems after spontaneous abortion.